Komunikasi Politik dan Peran Media dalam Pemilihan Umum - Nurhayati, Meti (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
General elections are an important stage where political communication and the media play a crucial role in shaping public opinion and community participation. This research investigates the impact of political communication and the role of the media in elections, with a focus on how political messages are delivered, received and influence voters. Through an in-depth literature review and empirical data analysis, this research finds that the media has a significant influence in shaping voter perceptions, especially through the concepts of framing and agenda setting. Social media, while playing an important role in disseminating political information, also brings new challenges such as filter bubbles that can limit diversity of opinion. Effective political communication has proven crucial in influencing voter participation. Although this study provides valuable insights, limitations of the study need to be acknowledged, and recommendations provided for future research. In conclusion, a deep understanding of the relationship between political communication, media, and voter participation is key to supporting a healthy and democratic election process.